2011
DOI: 10.1177/0891243211416113
|View full text |Cite
|
Sign up to set email alerts
|

Men Bring Condoms, Women Take Pills

Abstract: The most popular form of reversible contraception in the United States is the female-controlled hormonal birth control pill. Consequently, scholars and lay people have typically assumed that women take primary responsibility for contraceptive decision making in relationships. Although many studies have shown that men exert strong influence in couple’s contraceptive decisions in developing countries, very few studies have considered the gendered dynamic of contraceptive decision making in developed societies. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 32 publications
4
54
0
Order By: Relevance
“…In Western Europe, 58.9 per cent of couples in which the woman is aged 15-49 use the pill, contraceptive injections, implants or intrauterine devices, compared with 2.9 per cent relying on vasectomy, 6.3 per cent on tubal ligation and 7.6 per cent on condom use (United Nations, 2013). However, on the other hand, the observation that also the uptake of female sterilization exceeds that of male sterilizationalthough both are similarly effective and the latter implies lower physical and financial costs (Shih et al, 2011)-indicates that contraceptive choice is not purely a product of availability constraints (Fennell, 2011). It has been suggested that contraception shifts from being an individual's own responsibility and a means to protect him/herself against unintended pregnancy in the beginning of a relationship, toward a shared responsibility that is influenced by broader relationship dynamics in long-term relationships.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In Western Europe, 58.9 per cent of couples in which the woman is aged 15-49 use the pill, contraceptive injections, implants or intrauterine devices, compared with 2.9 per cent relying on vasectomy, 6.3 per cent on tubal ligation and 7.6 per cent on condom use (United Nations, 2013). However, on the other hand, the observation that also the uptake of female sterilization exceeds that of male sterilizationalthough both are similarly effective and the latter implies lower physical and financial costs (Shih et al, 2011)-indicates that contraceptive choice is not purely a product of availability constraints (Fennell, 2011). It has been suggested that contraception shifts from being an individual's own responsibility and a means to protect him/herself against unintended pregnancy in the beginning of a relationship, toward a shared responsibility that is influenced by broader relationship dynamics in long-term relationships.…”
Section: Introductionmentioning
confidence: 99%
“…The question can be raised whether contraceptive responsibility should be perceived as a burden or an indication of lower power, versus as a way of holding control or an indication of higher power. Following Fennell (2011) and Bertotti (2013), we apply the theoretical lens of the gendered division of labour to partners' roles in contraceptive decision-making in order to formulate two contrasting hypotheses.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations